THE EFFECTIVENESS OF COOPERATIVE LEARNING IN ENGLISH LANGUAGE CLASSROOMS - Lolakhon Nazarova (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract: Cooperative learning has gained significant attention as an effective instructional approach in English language classrooms. This study examines the impact of cooperative learning strategies on students’ language proficiency, motivation, and classroom  interaction.  Drawing  on  existing  empirical  research  and  theoretical frameworks, the article highlights how cooperative learning enhances communicative competence, fosters learner autonomy, and improves academic achievement in English as a Foreign Language (EFL) contexts. The findings suggest that cooperative learning, when  properly  implemented,  contributes  positively  to  both  linguistic  and  social outcomes in English language education.